Design and development of the FMCW Radar Scene Generator - Dwi Handayani, Dini Oktarina; Sediono, Wahju; Shah , Asadullah (2012)
Like other radar systems, Frequency Modulated Continuous Wave (FMCW) maritime radar can measure simultaneously the range, velocity, reflectivity and azimuth of targets on the sea. However, compared with conventional pulse radar, FMCW radar has many advantages. It is relatively small and simple, offers high resolution, provides data over wide bandwidths, and is relative inexpensive. On the other hand, the fast development in technologies of radar, electronic charts and further navigational aids requires permanent training. Such training can be conducted with the aid of a radar simulator. The benefit of using a radar simulator is that the radar environment is electronically synthesized, and therefore exactly repeatable. Furthermore, a good physics-based FMCW radar simulator requires a radar scene generator. This scene generator will provide a real-world test and training environment for the operation of the simulated radar system. The aim of this work is to develop a two-dimensional FMCW radar scene generator that can be used as an aid in the ship navigation training. In this work a suitable graphical user interface (GUI) is also designed and developed. Using this GUI the user can easily generate static and dynamic components of the radar scene generator.